On the breakaway oxidation of Fe9Cr1Mo steel in high pressure CO2. (15th May 2017) - Gong, Y.; Young, D.J.; Kontis, P.; Chiu, Y.L.; Larsson, H.; Shin, A.; Pearson, J.M.; Moody, M.P.; Reed, R.C.
Abstract: Fundamental insights into the mechanism of breakaway oxidation in Fe9Cr1Mo steel are deduced, through advanced characterisation and modelling. Degradation at 600 °C/∼42 bar CO2 for ∼20, 000 h is emphasised: conditions relevant to components such as the finned superheater tubes used for advanced gas-cooled nuclear reactors. It is shown that such conditions are sufficient to cause carbon saturation of the metallic substrate, as confirmed by direct observation of extensive carbide precipitation but also numerical analysis of the carbon transport. Thus the observation of graphite precipitation close to the scale/metal interface is rationalised. Nonetheless, the activity of carbon at the scale/metal interface does not reach unity – with respect to graphite – at time zero. A modelling method is proposed which accounts for this kinetic retardation of the attack; this can be used to interpolate across the regimes within which breakaway oxidation is prevalent. It is a plausible model for extrapolation to the lower temperatures relevant to service conditions and is suitable for lifetime estimation – so-called 'remnant life analysis' – of such safety-critical components when prone to this form of attack. Graphical abstract: Image 1